Progressive Stages or Levels of Technical Reading with Sample Reading Components Indicator: For Fourth Year B. Tech Students - Ms.Sahana Edwin, Dr. K.Ponnari Lakshmi, Ms.M. Indrani, Ms.Dasari Yuvarani, Mr.Nalluri Babu Rao, Dr. Sabitha Kumari Francis (South Eastern European Journal of Public Health, 2025)
The researchers are interested in finding the technical reading proficiency of fourth-year students. Hence the sample technical scripts are distributed and assessed for their reading efficacy. The entire class of students is subjected to the technical reading using the literary indicators. However, the class students are not divided into early-stage readers, transitional readers, and fluent readers. The researchers noticed the development of reading skills among students and the percentage is taken into account. The paper also helps the teachers to exercise a self-reflective assessment of their teaching every semester.